Versioning: Go Vertical in a Horizontal Market?. Issue 2 (2nd April 2016) - Dey, Debabrata; Lahiri, Atanu
Abstract: The issue of versioning of information goods has resurfaced, in part as a result of the recent popularity of downloadable contents (DLC) among video game manufacturers. The central idea behind the DLC strategy, zero-day DLCs in particular, is that consumers who find the base version of a game to be sufficiently close to their tastes would want more of its capabilities and would pay a premium to upgrade by purchasing a DLC. To better understand the implications of such a product-line strategy, in this work, we combine the literature on versioning with that on consumer learning. In doing so, we uncover an interesting economic phenomenon that, for an experience good, a manufacturer's desire to vertically differentiate could actually stem from its inability to otherwise elicit unobserved heterogeneity in consumers' perceived fit. In other words, we generalize versioning to accommodate both vertical and horizontal heterogeneity.